Hospital Efforts in Fulfilling Patients' Rights to Emergency Unit Health Services - Rifla, Cici; sni Syam, M. (Blantika: Multidisciplinary Journal, 2024)
A hospital is a health service facility that provides complete individual health services through promotive, preventive, curative, rehabilitative and/or palliative health services by providing inpatient, outpatient and emergency services. The Emergency Department (IGD) is a hospital unit that provides first care to patients. Emergency Services are medical actions required by Emergency Victims/Patients immediately to save lives and prevent disability. The current difficulty of society is expensive health financing. Not only because of the doctor, but to reach health facilities and infrastructure you also have to make a lot of effort. We can see in several cases of patient refusal in the ER at hospitals in several regions of Indonesia how difficult it is for people to get optimal health services. The method used is the Normative Juridical Method which aims to find legal regulations regarding hospitals in their efforts to treat emergency patients. The problem formulation that the author can put into this paper is how to implement and optimize hospital efforts to fulfill patients' rights to health services in the emergency unit. The results of the author's research are that in order to optimize the fulfillment of patient rights, hospitals are required to form internal hospital regulations and require hospitals to implement good corporate governance and good clinical governance.